Dampak Pengolahan Air Lindi terhadap Kualitas Air Sungai dan Sumur di Sekitar TPA Regional Piyungan Yogyakarta - Harnung Wulan Dari; Suhartini Suhartini (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
Water is the main need for life, so the quality of the water used in life needs to be known. The objectives of this research are to determine the leachate management system at the IPL, determine efficiency of leachate water treatment performance at IPL, and determine impact of leachate water quality at Piyungan Regional Landfill on the river and wells water quality around the landfill. This research is quantitative descriptive research conducted at Piyungan Regional Landfill and its surroundings in April-July 2023. The data collected were results of physical, chemical, and biological parameters of the IPL Inlet and Outlet leachate water quality, Opak River after the IPL Outlet, and 3 samples of well water from the surrounding community representing distance from the landfill. The data collection methods used are observation, documentation, and analysis of water quality in the laboratory. The data obtained were analyzed using descriptive methods and compared with quality standards set by the Government. The results showed that: The leachate water management system at the IPL uses 8 water treatment tanks include: a bar screen, inlet, coagulation tank, equalization tank, sedimentation tank, SDB, ABR, aeration tank, maturation tank, chlorination tank, and Outlet. The efficiency of leachate water treatment performance at the IPL is not effective and efficient in processing leachate water. The quality of leachate water affects the water quality of the Opak River and wells around the landfill, on chemical parameters TDS, BOD, COD, DO, and microbiological parameters Total Coliform, therefore, the Regional Government need to evaluate and improve the IPL. Communities around the Landfill that use well water as their main need must be filtered and boiled.